Perlindungan Driver terhadap Kebijakan Fitur Hemat Ojek Online di Kota Medan Perspektif al-Maṣlaḥah - Jannah, Nurul Miftahul; Yazid, Imam (Borneo : Journal of Islamic Studies, 2025)
The implementation of the “hemat” (economy) feature in online ride-hailing services represents a digital promotion strategy aimed at attracting consumers through fare reductions. However, this policy creates systemic pressure on drivers, particularly regarding income and workload. This study aims to analyze the implementation of the feature and assess the form of driver protection from the perspective of al-maṣlaḥah. A qualitative approach with an empirical legal design was employed. Data were collected through semi-structured interviews with 20 Grab and Gojek drivers in Medan City, as well as a review of Islamic legal literature and digital transportation policies. The findings reveal that most drivers feel compelled to activate the feature due to algorithmic pressure, resulting in decreased net income and increased working hours without adequate social protection. The al-maṣlaḥah analysis indicates that the feature does not fulfill the principles of shar‘ī benefit, as it fails to protect the drivers’ lives (ḥifẓ al-nafs) and wealth (ḥifẓ al-māl), and contradicts the principles of riḍā bi al-tarāḍī (mutual consent), the prohibition of gharar (uncertainty), and the legal maxim lā ḍarar wa lā ḍirār (no harm and no reciprocating harm) in Islamic business ethics. The study recommends that online ride-hailing platforms revise or discontinue the “hemat” feature, improve order distribution and fare deduction schemes, enhance transparency and partner participation, and encourage government regulations that ensure fair working conditions for the informal sector, aligning with justice, protection, and the balance of rights in digital business ethics.